User Satisfaction Evaluation of the Mental Health Risk Detection Feature on the Satu Sehat Application Using the End User Computing Satisfaction (EUCS) Method - Naila Khumaira; Maula Ismail Mohammad; Lina Khasanah; Bambang Karmanto (International Journal of Health and Pharmaceutical (IJHP), 2026)
Adolescent mental health issues, particularly anxiety and depression, remain high among Indonesian high school students, yet accessible early detection tools are limited. This study evaluated user satisfaction with the mental health risk detection feature in the SatuSehat application using the End-User Computing Satisfaction (EUCS) model among students at SMA Negeri 1 Beber, Cirebon. Using a cross-sectional, descriptive-analytical quantitative design, a quota sample of 96 students (71% female, aged 17-18 years) completed a 24-item Likert scale questionnaire validated to measure the five dimensions of the EUCS. Data were analyzed using Spearman Rank correlation due to non-normal distribution. The results showed high satisfaction (mean=4.07/5), with the highest format (4.17) and the lowest timeliness (3.92). All dimensions were strongly positively correlated with satisfaction (r=0.688-0.860, p<0.001), with ease of use being the strongest. In conclusion, the SatuSehat feature effectively satisfies adolescent users for mental health screening.